2017
DOI: 10.12816/0039672
|View full text |Cite
|
Sign up to set email alerts
|

Association between Chlamydia Trachomatis Cervicitis and Preterm Labor

Abstract: Background: Preterm labor (PTL) is a major determinant of neonatal morbimortality with adverse consequences for health. The causes are multifactorial, with intrauterine infection probably explaining most of these outcomes. It is believed that infection with Chlamydia trachomatis (CT) is also involved in PTL. Objective: To compare the prevalence of chlamydia trachomatis cervicitis in women with preterm labor and control at term. Methods: This was a case-control study conducted at Ain Shams University Maternity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It has been shown that in women with history of preterm birth there is 17.8% chance of next preterm and after two preterm there are 4.4% chances. Similarly study of Mohamed SS et al 13 observed 14% chance of next PTL but Derakhshi et al 12 observed high chances of 31.2%. Pandey et al 14 and Singh et al 15 showed same results of 14% whereas Leal et al 16 and Wagura et al 17 showed higher associated of previous preterm of 27.9% and 35% respectively.…”
Section: Resultsmentioning
confidence: 88%
“…It has been shown that in women with history of preterm birth there is 17.8% chance of next preterm and after two preterm there are 4.4% chances. Similarly study of Mohamed SS et al 13 observed 14% chance of next PTL but Derakhshi et al 12 observed high chances of 31.2%. Pandey et al 14 and Singh et al 15 showed same results of 14% whereas Leal et al 16 and Wagura et al 17 showed higher associated of previous preterm of 27.9% and 35% respectively.…”
Section: Resultsmentioning
confidence: 88%
“…in endocervical infection and its association with placental inflammation ( 82 ), pPROM and sPTB ( 83 ). Similarly, the prevalence of C. trachomatis has been observed to increase among women experiencing preterm labor, particularly those with PTB, compared with women who gave birth at term ( 84 ). This became apparent when women with C. trachomatis receiving antibiotic treatment showed a reduced incidence of sPTB ( 85 ).…”
Section: Introductionmentioning
confidence: 98%
“…The prevalence of C. trachomatis cervicitis in women with PTL was significantly higher in patients with PTBs than in women with term deliveries ( 48 ). Another study showed that cervicitis among pregnant women was commonly caused by C. trachomatis .…”
Section: Cervical Infections Promote Preterm Birthmentioning
confidence: 96%